Regioselective nitration of cumene to 4-nitro cumene using nitric acid over solid acid catalyst - Mathew, Sanyo M.; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Catalysis Communications, 2006)
The regioselective nitration of cumene to 4-nitro cumene (4-NC) has been carried out using 70% nitric acid over MoO3/SiO2 solid acid catalyst with high conversion (62%) and selectivity (68%) for 4-NC. A series of MoO3/SiO2 catalysts with different MoO3 loadings (1-20 mol%) were prepared by sol-gel technique and characterized using different characterization techniques. XRD analysis revealed the amorphous nature of the catalyst up to 10-mol% MoO3 loading and formation of alpha-MoO3 crystalline phase on amorphous high surface area mesoporous silica support at higher MoO3 loading. Maximum conversion and selectivity has been obtained with slower addition of nitric acid and simultaneous azeotropic removal of water formed during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: cumene; nitration; ring nitration; side chain nitration; solid acid catalyst

Nitration and amination of polyphenylene oxide: synthesis, gas sorption and permeation analysis - Bhole, Yogesh S.; Karadkar, Prasad B.; Kharul, Ulhas K. (European Polymer Journal, 2007)
A high degree of nitration of polyphenylene oxide (PPO) was successfully achieved by carefully optimizing synthetic protocol. The reduction of nitro group to amino could be done quantitatively. The physical properties of formed polymers were investigated and correlated with gas sorption and permeation properties. The formed polymers were amorphous in nature as revealed by wide angle X-ray diffraction spectra. An increase in the packing density in comparison to unsubstituted PPO as a result of induced polarity was indicated by lowering of fractional free volume and d-spacing. The substitution by either nitro or amino group increased the chain stiffness as revealed by the dynamic mechanical analysis. Though both, nitro and amino group substitution on PPO led to a decrease in pure gas permeability, the selectivity of various gas pairs was increased by these substitutions. The gas sorption analysis revealed that both, solubility selectivity and diffusivity selectivity were increased by these polar group substitutions. The nitro group substitution was more effective in improving solubility selectivity, while amino group substitution was more effective in improving diffusivity selectivity. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Amination; nitration; permeation; polyphenylene oxide; Sorption

Continuous flow nitration in miniaturized devices - Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2014)
This review highlights the state of the art in the field of continuous flow nitration with miniaturized devices. Although nitration has been one of the oldest and most important unit reactions, the advent of miniaturized devices has paved the way for new opportunities to reconsider the conventional approach for exothermic and selectivity sensitive nitration reactions. Four different approaches to flow nitration with microreactors are presented herein and discussed in view of their advantages, limitations and applicability of the information towards scale-up. Selected recent patents that disclose scale-up methodologies for continuous flow nitration are also briefly reviewed.
Keywords: continuous flow; flow chemistry; microreactors; nitration; nitric acid; Tubular reactor

Discontinuous two step flow synthesis of m-aminoacetophenone - Tibhe, Jagdish; Sharma, Yachita; Joshi, Ramesh A.; Joshi, Rohini R.; Kulkarni, Amol A. (Green Processing and Synthesis, 2014)
The continuous flow nitration of acetophenone followed by reduction of the meta isomer has been demonstrated using simple tubular reactors. Because of ease of separation of the desired isomer from the first step, both steps are made continuous, but separately. The continuous flow nitration was carried out in a safe manner in a shorter reaction time than the conventional approach. The choice of micromixer was seen to affect the performance of the nitration reaction. The effect of different parameters on the yield of the desired product was studied. The reduction step with sodium sulfide was found to be economical and could be carried out efficiently at 70 degrees C using sodium sulfide in ethanol, using a silicone tube. Both steps were demonstrated for several hours, yielding a sufficiently large quantity (similar to 100 g) of m-aminoacetophenone at lab scale in a single day using simple tubular reactors.
Keywords: acetophenone; continuous flow synthesis; microreactor; nitration; reduction

Evaluation of multipoint dosing strategy in a miniaturized tubular reactor: nitration of salicylic acid - Debnath, Soujoy; Kienle, Achim; Kulkarni, Amol A. (Chemical Engineering & Technology, 2014)
A 2D non-isothermal reaction engineering model for a tubular reactor was developed for a complex reaction network of salicylic acid nitration. The influence of different operating and design parameters was studied to minimize the amount of secondary nitration products and limit the maximum temperature inside the reactor. Critical temperature effects were observed for larger reaction tubes, whereas close to isothermal conditions were perceived in smaller tubes. With single-point dosing of both reactants, complete conversion can be achieved but formation of secondary nitration products cannot be avoided. For a given number of dosing points, a suitable combination of the operating parameters allowed to achieve complete conversion and better yield of the desired product.
Keywords: Multipoint injection; nitration; Plug-flow reactor; Salicylic acid; Tubular reactor

Design and scale-up of continuous di-nitration reaction using pinched tube flow reactor - Hussain, Arshad; Sharma, Mrityunjay; Patil, Suneha; Acharya, Roopashree B.; Kute, Mahesh; Waghchaure, Aishwarya; Kulkarni, Amol A. (Journal of Flow Chemistry, 2021)
Scale-up of the di-nitration reaction for synthesis of selective herbicide pendimethalin using only nitric acid in continuous flow is presented in this work. This work showcases an approach for smooth scale-up for an herbicide for a production capacity of 50 kg/day using a pinched tube reactor. The approach begins with the batch experiments followed by flow synthesis using a 1/8-inchSS316 helical coil tube where kinetics of the di-nitration was determined, and process optimization was done. Systematic approach was followed for quantification of heat transfer, mass transfer and residence time distribution and scale-up. Detailed scale-up methodology is presented with effect of relevant parameters for successful scale-up. Modular pilot plant with inline quenching, extraction and separation are some of the salient features presented in this work.
Keywords: continuous flow; nitration; Pinched tube; RTD; scale-up